Eliciting deliberative and implemental mindsets in audit planning - Rixom, Brett A.; Plumlee, David (Contemporary Accounting Research, 2023)
Abstract There is concern that rather than critically deliberating specific circumstances, auditors focus on selecting and documenting defensible audit positions. Currently, subordinate auditors perform tasks mindful that they will be accountable for their work both inside (e.g., partners) and outside (e.g., PCAOB) the firm and adopt “implementation intentions” based on previous review experiences to guide their performance. In the context of fraud‐detection planning, we consider an alternative approach in which subordinate auditors work under contingent reward agreements under which they will be compensated for effective fraud‐detection plans. Lacking an anticipated course of action, they invoke a “deliberative mindset” in order to create a task strategy. In an experiment, auditors completed a fraud‐detection planning task under contingent rewards, accountability, or anonymity. We find that auditors operating under contingent rewards used deliberative mindsets. They were better able to identify potential fraud, select more effective procedures, and plan more hours for effective procedures. Auditors under accountability completed the planning task based on implementation intentions. They focused on broadly increasing audit hours across procedures, including allocating significantly more hours to less effective procedures. Mediation analysis shows that improved planning performance resulted from the use of deliberative mindsets and not implementation intentions.